Fast Atomic Diffusion: Bulk and Short‐Circuit Anion Diffusion in Epitaxial Fe2O3 Films Quantified Using Buried Isotopic Tracer Layers (Adv. Mater. Interfaces 9/2021). Issue 9 (7th May 2021) - Kaspar, Tiffany C.; Taylor, Sandra D.; Yano, Kayla H.; Lach, Timothy G.; Zhou, Yadong; Zhu, Zihua; Kohnert, Aaron A.; Still, Evan K.; Hosemann, Peter; Spurgeon, Steven R.; Schreiber, Daniel K.
Abstract : Fast atomic diffusion through structural defects in Fe2 O3 is directly imaged for the first time at the sub‐nanometer level by atom probe tomography. In article number 2001768 by Tiffany C. Kaspar and co‐workers, model epitaxial and defect‐rich thin films of Fe2 O3 are deposited with molecular beam epitaxy, incorporating a tracer layer of 18 O within the film itself. Atomic‐level self‐diffusion is then visualized and quantified in 3D by APT, revealing ≈10 4 times faster oxygen diffusion along structural flaws than through the pristine lattice.